Metagenomic Analysis of Antarctic Ocean near the King Sejong Station Reveals the Diversity of Carotenoid Biosynthetic Genes - Cho, Woo Yeon; Lee, Pyung Cheon (Microorganisms, 2024)
Carotenoids, biotechnologically significant pigments, play crucial biological roles in marine microorganisms. While various environments have been explored to understand the diversity of carotenoids and their biosynthesis, the Antarctic Ocean remains relatively under-investigated. This study conducted a metagenomic analysis of seawater from two depths (16 and 25 m) near the King Sejong Station in the Antarctic Ocean. The analysis revealed a rich genetic diversity underlying C40 (astaxanthin, myxol, okenone, spheroidene, and spirilloxanthin), C30 (diaponeurosporene, diapolycopene, and staphyloxanthin), and C50 (C.p. 450) carotenoid biosynthesis in marine microorganisms, with notable differential gene abundances between depth locations. Exploring carotenoid pathway genes offers the potential for discovering diverse carotenoid structures of biotechnological value and better understanding their roles in individual microorganisms and broader ecosystems.
Keywords: carotenoids; metagenome; microbial diversity